EFFECTS OF EXERCISES ON REPETITIVE STRAIN INJURIES OF HAND IN MILKMEN - PROF.TUSHAR J PALEKAR,; ANIRUDHA VAIDYA,; SOUMIKBASU, (International Journal of Pharma and Bio Sciences, 2015)
Repetitive strain injury (RSI) is a common and serious occupational health problem worldwide. About 60% of all occupational injuries are caused by repetitive strain.41 milkmen were taken from Indian dairy farm Pimpri, Pune found symptomatic for RSI, and 9 asymptomatic milkmen were taken. All 50 milkmen were treated with exercise protocol for 3 weeks. Disabilities of the Arm, Shoulder and Hand(DASH )questionnaire and VAS Scale were given to fill up (Pre-rehabilitation) and data collected and analyzed. After 3 weeks of hand strengthening exercises for 20-25 mins daily, all 50 milkmen were assessed with same DASH questionnaire and VAS, and were statistically analyzed. The incidence of the repetitive strain injuries of hand in milkmen was 82%. The decided exercise protocol showed significant improvement in DASH score and VAS score.